Biofuel’s Sustainable Development under the Trilemma of Energy, Environment and Economy - Liu, Heqing (Problemy Ekorozwoju, 2015)
Biofuel helps to overcome energy shortages, and to improve the environment, as well as to increase job opportunity. So, on the one hand, biofuel solves the above mentioned problems; on the other hand, it brings new challenges to the fields of energy, environment and economy. The development of biofuel not only needs technological support, but also needs policy guidance. The paper discusses government’s policy to support biofuel’s development in a sustainable way.